STRATEGI KOMUNIKASI PENERIMAAN MAHASISWA BARU DI UNIVERSITAS MUHAMMADIYAH CIREBON - Teddy Dyatmika (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2018)
Muhammadiyah University of Cirebon (UMC) is a university that is currently developing in the region III Cirebon (Cirebon Kota / Kab, Majalengka, Indramayu and Kuningan) today. Bagging "B" accretion should be an attraction for prospective new students to join the main campus located on Jl. These Cirebon Sources. Moreover, Cirebon Muhammadiyah University has several advantages over other universities. Strategic campus location, relatively affordable tuition fees, is an added value for prospective new students to determine their choice to study at Muhammadiyah University in Cirebon. However, in fact, not all fresh graduates look at UMC as an alternative university for them to study. Keyword: Students, Promotion, Communication Strategy